Service users' experiences of the treatment decision-making process in psychosis: A phenomenological analysis. Issue 4 (1st October 2016) - Stovell, Diana; Wearden, Alison; Morrison, Anthony P.; Hutton, Paul
Abstract : Objectives: We aimed to explore the treatment decision-making experiences of individuals with psychosis, and their implications for increasing service users' autonomy through clinical practice and research. Design: A qualitative design was used to explore in depth service users' experiences of treatment decision-making. Method: People with non-affective psychosis took part in semi-structured interviews that sought to elicit rich descriptions of their subjective experiences of treatment decision-making encounters. These were analysed using Interpretative Phenomenological Analysis (IPA). Results: The interviews of seven service users with multiple experiences of treatment for psychosis were analysed. Four themes emerged around influences on treatment decision-making: (1) a need to feel listened to; (2) psychotic experiences, treatment and stigma; (3) communication and support; (4) differing conceptions of recovery. There was an over-arching theme of empowerment. Conclusions: Influences on participants' empowerment emerged at multiple levels, from their sense of self-worth to prevailing social constructions around psychosis. Service users' participation in decision-making about treatment for psychosis might be enhanced where clinicians are able to pay close attention to disempowering aspects of their experience. The development of more comprehensive models of decisional capacity may support this endeavour.